Three-month functional outcomes of acute ischemic stroke in patients with chronic renal function impairment. - Dina Hemmati; Negin Eissazade; Shayan Eghdami; Zahra Mirzaasgari; Atefeh Amouzegar (PLoS ONE)
Background Chronic renal function impairment (RFI) increases the risk of acute ischemic stroke (AIS), greater stroke severity, and post-stroke disability and mortality. Objective We aimed to assess the three-month functional outcomes of AIS in patients with chronic RFI. Methods In this prospective study, stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS), and functional outcomes were assessed using the modified Rankin Scale (mRS). Outcomes were analyzed based on estimated glomerular filtration rate (eGFR). Results Among the 205 patients included (median age: 70 years, IQR: 61-82), 123 (60%) were male. Patients with lower eGFR had higher NIHSS scores (more severe strokes) and higher mRS scores at both baseline and three months (poorer functional outcomes). Based on a logistic regression model adjusted for confounding factors, higher eGFR was significantly associated with good three-month functional outcomes (adjusted OR = 2.634, 95% CI [1.207, 5.748], p = 0.015). Conclusions Chronic RFI is associated with more severe strokes and poorer baseline and three-month functional outcomes after AIS. Future research should explore targeted management strategies to improve post-stroke recovery in this population.